Activated carbon fiber composite material, preparation method and application of activated carbon fiber composite material in gaseous methyl iodide adsorption
By uniformly riveting metal ions on activated carbon fibers and loading MOFs, combined with high-temperature auxiliary ligand reverse diffusion and tannin acid etching technology, the problem of low adsorption efficiency of gaseous methyl iodide in high humidity environments is solved, and the uniform load and firm combination of MOFs on ACF is achieved, improving the adsorption performance.
Patent Information
- Application Number
- CN202510010009.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-22
AI Technical Summary
The prior art has low adsorption efficiency of gaseous methyl iodide in high humidity environments, and the uniform loading and bonding of metal-organic framework materials (MOFs) on activated carbon fibers (ACFs) are not strong, which affects the adsorption performance.
By soaking the metal ion solution on the activated carbon fibers, the metal ions are uniformly riveted, and then placed in a polysulfone-based film, the coordination reaction is carried out to load MOFs. The uniformity and firmness of the MOFs on the surface and internal distribution of the ACF are improved using a high-temperature auxiliary ligand reverse diffusion strategy and tannin etching.
The efficient adsorption performance of gaseous methyl iodide under high humidity conditions is achieved, ensuring uniform loading and firm combination of MOFs on ACF, and improving the overall performance of adsorbent materials.
Smart Images

Figure CN119857465A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of gas adsorption, and in particular relates to an activated carbon fiber composite material, a preparation method and application of the composite material in gaseous methyl iodide adsorption. Background Art
[0002] In order to achieve sustainable development, the development and efficient use of clean energy has become one of the hot topics of research, and nuclear energy is one of them. Nowadays, many developed countries have begun to try to use nuclear energy on a large scale to generate electricity, but the resulting nuclear leakage accidents have also attracted the attention of researchers. Among the extremely dangerous radionuclides, radioactive methyl iodide has attracted much attention due to its volatility and toxicity.
[0003] At present, the methods for capturing gaseous methyl iodide can be divided into two categories: wet scrubbing and dry adsorption. Compared with wet scrubbing, dry adsorption has been adopted by many researchers due to its advantages such as high removal efficiency, low cost and simple operation. In the application process, adsorption materials with good separation selectivity and high adsorption rate are the core of dry adsorption, which determines the selective permeability of adsorption, process design and the final adsorption applicable system.
[0004] However, in a high humidity environment, the adsorption efficiency of gaseous methyl iodide is affected by humidity. In recent years, metal-organic frameworks (MOFs), which are composed of metal ions or metal clusters and organic linking ligands, have attracted much attention due to their large specific surface area, high porosity, high crystallinity, stable structure and performance, and adjustable pore size. Although MOFs have many advantages in adsorption, their powdery morphology brings great inconvenience to practical applications and recycling. Activated carbon fiber (ACF) is the third generation of activated carbon materials. It has become the preferred carrier material for many researchers because of its rich micropores, large specific surface area, and easy processing into fabrics and felts.
[0005] At present, the method of combining MOFs with ACF in the literature is mainly through hydrothermal or solvothermal method, which is to directly immerse the ACF in a mixed solution of MOF metal and ligand, and then load the MOFs onto the ACF by high-temperature heating. However, it is difficult for MOFs to be evenly loaded on the ACF, which affects its function.
[0006] Therefore, it is of great significance to develop a MOF / ACF composite material with excellent adsorption performance of gaseous methyl iodide under high humidity conditions. Summary of the invention
[0007] The purpose of the present invention is to at least partially solve the above-mentioned technical problems, and aims to provide an activated carbon fiber composite material, a preparation method and its application in the adsorption of gaseous methyl iodide. By uniformly loading MOFs with excellent crystal form on activated carbon fibers, efficient adsorption of gaseous methyl iodide can be achieved in a high humidity environment.
[0008] A first aspect of the present invention provides a method for preparing an activated carbon fiber composite material, the preparation method comprising the following steps:
[0009] S1. Using a metal ion solution to soak the activated carbon fiber, so that the metal ions in the metal ion solution are evenly riveted on the activated carbon fiber;
[0010] S2. Place the activated carbon fiber obtained in step S1 on the polysulfone layer of the polysulfone-based membrane, and then place the other layer of the polysulfone-based membrane downward in the organic ligand solution so that the organic ligand solution immerses the polysulfone-based membrane but does not contact the activated carbon fiber, and then carry out coordination reaction under sealing conditions to obtain an activated carbon fiber composite material.
[0011] In some embodiments, the metal ion solution is one of zinc nitrate hexahydrate solution, cobalt nitrate hexahydrate solution and copper sulfate pentahydrate solution, and the ligand solution is a methanol solution of 2-methylimidazole.
[0012] In some embodiments, the polysulfone-based membrane is formed by laminating a polysulfone layer and a non-woven fabric layer.
[0013] In some embodiments, in step S1, the soaking time is 1.5-2.5 hours.
[0014] In some embodiments, step S2 specifically includes the following steps:
[0015] S21. The polysulfone-based membrane is fixed to the hollow frame, wherein the polysulfone layer of the polysulfone-based membrane faces upward;
[0016] S22. The activated carbon fiber obtained in step S1 is placed on the polysulfone layer of the polysulfone-based membrane, and then translated into a reactor containing an organic ligand solution, so that the organic ligand solution submerges the polysulfone-based membrane, but the liquid level does not exceed the height of the hollow frame;
[0017] S23. The reactor is sealed and placed in an oven for coordination reaction. After the reaction is completed, the reactor is cooled to room temperature and the activated carbon fiber after the reaction, i.e., the activated carbon fiber composite material, is taken out.
[0018] In some embodiments, in step S2, the temperature of the coordination reaction is 120°C-160°C, and the time is 2-4 hours.
[0019] In some embodiments, the preparation method further comprises:
[0020] The activated carbon fiber composite material prepared in step S2 is placed in a tannic acid solution, heated under a sealed condition for reaction, and after the reaction is completed, the activated carbon fiber composite material is taken out. Preferably, the concentration of the tannic acid solution is 0.02-0.03 g / mL, the heating reaction temperature is 140-160°C, and the reaction time is 0.5-1.5 h.
[0021] The second aspect of the present invention provides an activated carbon fiber composite material prepared by the above-mentioned preparation method.
[0022] The third aspect of the present invention provides a use of the above-mentioned activated carbon fiber composite material in the preparation of an adsorption material.
[0023] In some embodiments, the adsorbent material is used to adsorb gaseous methyl iodide.
[0024] In some embodiments, the adsorbent material is used to adsorb gaseous methyl iodide under high humidity conditions.
[0025] The activated carbon fiber composite material, preparation method and application thereof in gaseous methyl iodide adsorption according to the embodiments of the present invention have the following advantages:
[0026] (1) The present invention utilizes the control effect of the PSf-based membrane and adopts a high-temperature assisted ligand reverse diffusion strategy to allow the organic ligand solution to slowly penetrate and diffuse into the ACF, effectively controlling the reaction rate of the ligand and the metal, ensuring the good crystallinity of MOFs (such as ZIF-8) while improving the uniformity and firmness of the distribution of MOFs on the surface and inside of the ACF. The obtained activated carbon fiber composite material has good gaseous methyl iodide adsorption performance under high humidity conditions.
[0027] (2) The present invention cleverly uses a hollow frame to separate the activated carbon fibers with metal ions fixed thereto from the organic ligand solution, thereby avoiding homogeneous nucleation between the metal ions and the organic ligands, better controlling the reaction rate between the ligands and the metal, and being more conducive to improving the uniformity of the distribution of MOFs on the surface and inside of the ACF.
[0028] (3) The present invention further adopts tannic acid etching, and controls the concentration of the tannic acid solution, the reaction temperature and the time to make the MOFs crystals loaded on the activated carbon fiber hollow due to etching, so that the specific surface area of the ZI F-8 crystals reaches the maximum. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] These and / or other aspects and advantages of the present invention will become apparent and readily understood from the following description of the preferred embodiments in conjunction with the accompanying drawings, in which:
[0030] Figure 1A schematic diagram of a preparation method provided by an embodiment of the present invention;
[0031] Figure 2 Figure 1 is a picture of ZI F-8 / ACF-1 composite material; Figure (1) and Figure (2) are surface SEM images at different magnifications;
[0032] Figure 3 Figure 1 is a picture of ZI F-8 / ACF-2 composite material; Figure (1) and Figure (2) are surface SEM images at different magnifications;
[0033] Figure 4 Figure 1 is a picture of ZI F-8 / ACF-3 composite material; Figure (1) and Figure (2) are surface SEM images at different magnifications;
[0034] Figure 5 Figure 1 is a picture of ZI F-8 / ACF-4 composite material; Figure (1) and Figure (2) are surface SEM images at different magnifications;
[0035] Figure 6 Figure 1 is a picture of ZI F-8 / ACF-5 composite material; Figure (1) and Figure (2) are surface SEM images at different magnifications;
[0036] Figure 7 Figure 1 is a picture of ZI F-8 / ACF-6 composite material; Figure (1) and Figure (2) are surface SEM images at different magnifications;
[0037] Figure 8 Figure 1 is a picture of ZI F-8 / ACF-7 composite material; Figure (1) and Figure (2) are surface SEM images at different magnifications;
[0038] Fig. 9 The picture of 1%TA@ZI F-8 / ACF-3 composite material; wherein, Figure (1) and Figure (2) are surface SEM images at different magnifications;
[0039] Fig.10 The picture of 2%TA@ZI F-8 / ACF-3 composite material; wherein, Figure (1) and Figure (2) are surface SEM images at different magnifications;
[0040] Fig.11 The picture of 4%TA@ZI F-8 / ACF-3 composite material; wherein, Figure (1) and Figure (2) are surface SEM images at different magnifications;
[0041] Fig.12The static adsorption performance of gaseous methyl iodide of the ZI F-8 / ACF-1, ZI F-8 / ACF-2, ZI F-8 / ACF-3 and ZI F-8 / ACF-4 composite materials prepared in Example 1, Example 2, Example 3 and Example 4;
[0042] Fig.13 The gaseous methyl iodide static adsorption performance of the ZI F-8 / ACF-3, ZI F-8 / ACF-5, ZI F-8 / ACF-6 and ZI F-8 / ACF-7 composite materials prepared in Example 3, Example 5, Example 6 and Example 7;
[0043] Fig.14 The static adsorption performance of gaseous methyl iodide of 1% TA@ZI F-8 / ACF-3, 2% TA@ZI F-8 / ACF-3, and 4% TA@ZI F-8 / ACF-3 composite materials prepared in Example 8, Example 9, and Example 10. DETAILED DESCRIPTION
[0044] The technical solution of the present invention is further specifically described below by examples and in conjunction with the accompanying drawings. In the specification, the same or similar reference numerals indicate the same or similar components. The following description of the embodiments of the present invention with reference to the accompanying drawings is intended to explain the overall inventive concept of the present invention and should not be construed as a limitation of the present invention.
[0045] In an embodiment of the present invention, a method for preparing an activated carbon fiber composite material is provided, comprising the following steps:
[0046] S1. The activated carbon fiber is soaked in a metal ion solution so that the metal ions in the metal ion solution are evenly fixed on the activated carbon fiber to obtain activated carbon fibers fixed with metal ions.
[0047] S2. The activated carbon fiber riveted with metal ions is placed on the polysulfone layer of the polysulfone-based membrane, and then the other layer of the polysulfone-based membrane is placed downward in the organic ligand solution, so that the organic ligand solution immerses the polysulfone-based membrane but does not contact the activated carbon fiber, and then a coordination reaction is carried out under sealing conditions to obtain an activated carbon fiber composite material.
[0048] In some embodiments, the polysulfone-based membrane is formed by laminating a polysulfone layer and a non-woven fabric layer.
[0049] Activated carbon fiber is a hydrophilic material, and its adsorption of gaseous methyl iodide is poor under high humidity conditions. Loading MOF (such as ZIF-8) on the surface of activated carbon fiber can make the material hydrophobic, so that the material has excellent adsorption performance for gaseous methyl iodide under high humidity environment. The crystal structure of MOF, the uniformity of loading, and the specific surface area of the activated carbon fiber composite material obtained by loading MOF are important factors affecting the adsorption performance of the composite material for gaseous methyl iodine under high humidity environment.
[0050] In some embodiments, the method for preparing the activated carbon fiber composite material is:
[0051] S101. Soaking the activated carbon fiber in a metal ion solution so that the metal ions in the metal ion solution are evenly fixed on the activated carbon fiber, thereby obtaining activated carbon fibers fixed with metal ions.
[0052] S201. Fix the polysulfone layer of the polysulfone-based membrane on the hollow frame with the polysulfone layer facing upward.
[0053] S301. Place the activated carbon fibers with metal ions fixed thereto on the polysulfone layer of the polysulfone-based membrane, and then move the entirety of the activated carbon fibers horizontally into a reactor filled with an organic ligand solution, so that the organic ligand solution submerges the polysulfone-based membrane. However, the liquid level does not exceed the height of the hollow frame to ensure that the organic ligand solution does not directly soak the activated carbon fibers with metal ions fixed thereto.
[0054] The double-layer structure of the polysulfone layer and the non-woven fabric layer of the polysulfone-based membrane can control the rate at which the organic ligand enters the activated carbon fiber. The liquid level of the organic ligand solution does not exceed the height of the hollow frame. The purpose is to ensure that the organic ligand solution will not directly soak the activated carbon fiber riveted with metal ions, thereby preventing the organic ligand from reacting rapidly with the metal ions in the metal ion solution.
[0055] S401. The reactor is sealed and placed in an oven for coordination reaction. After the reaction is completed, the reactor is cooled to room temperature and the activated carbon fibers obtained by the reaction, namely, the activated carbon fiber composite material, are taken out.
[0056] Since in a mixed solution of metal ions and organic ligands, homogeneous nucleation is easy to occur between the two, while heterogeneous nucleation of metal ions and organic ligands on ACF is relatively difficult, the present invention first fixes the metal ions on the activated carbon fiber, and then places the activated carbon fiber with the metal ions fixed on the polysulfone layer of the polysulfone-based membrane, and then translates the entire thing into a reactor filled with an organic ligand solution, and through a high-temperature assisted ligand reverse diffusion strategy, the organic ligand solution slowly penetrates and diffuses into the ACF to react with the metal ions fixed on the ACF, effectively controlling the reaction rate of the ligand and the metal, ensuring good crystallinity of MOF (such as ZIF-8) while improving the uniformity and firmness of the distribution of MOF on the surface and inside of the ACF.
[0057] In some embodiments, Figure 1 As shown, in order to facilitate the operation, the preparation of activated carbon fiber composite materials can also be carried out by the following method:
[0058] S1. The PSf base membrane is tightly fixed on the hollow frame, wherein the smooth surface (polysulfone layer side) of the membrane faces upward, and then the ACF is placed on the polysulfone layer of the PSf base membrane in the hollow frame, wherein the PSf base membrane serves as a support, and then the metal ion solution is poured into the ACF and soaked until the ACF is fully immersed in the metal ion solution;
[0059] S2. After the immersion is completed, remove the excess metal ion solution, and move the whole body horizontally into the reactor containing the organic ligand solution, so that the organic ligand solution submerges the polysulfone base membrane (the solution level is higher than the PSf base membrane), but does not submerge the whole body (the liquid level does not exceed the height of the hollow frame). After sealing, put it into a blast oven for reaction. After the reaction is completed, wait for it to cool to room temperature, take out the ACF, wash the residual organic ligand with anhydrous methanol, and then put it into a vacuum oven for drying to obtain an activated carbon fiber composite material.
[0060] In some embodiments, the activated carbon fiber is immersed in the metal ion solution for 1.5-2.5 hours. If the immersion time is too short, for example, less than 1.5 hours, the metal ions riveted on the activated carbon fiber are too few. If the immersion time is too long, the metal ions riveted on the activated carbon fiber are too many, and the MOF formed by the ligand reaction is excessive, which will cover the micropores of the activated carbon fiber and affect the adsorption of gaseous methyl iodide by the composite material.
[0061] In a more preferred embodiment, the activated carbon fiber is immersed in the metal ion solution for 2-2.5 hours.
[0062] In some embodiments, the temperature for the coordination reaction is 120°C-160°C, and the time is 2-4 hours. The temperature of the coordination reaction affects the crystallinity of the MOF. The coordination reaction at a temperature of 120°C-160°C can obtain a MOF with excellent crystal form, for example, a MOF with a regular dodecahedral structure. Too high or too low a temperature cannot obtain a MOF with excellent crystal form, thereby affecting the adsorption performance of the composite material for gaseous methyl iodide.
[0063] In some embodiments, the metal ion solution is one of zinc nitrate hexahydrate solution, cobalt nitrate hexahydrate solution and copper sulfate pentahydrate solution, and the ligand solution is a methanol solution of 2-methylimidazole.
[0064] In some embodiments, zinc nitrate hexahydrate solution is used as the metal ion solution.
[0065] In some embodiments, the preparation method further includes: placing the activated carbon fiber composite material prepared in step S2 into a tannic acid solution, heating and reacting under sealed conditions, and after the reaction is completed, taking out the activated carbon fiber composite material, washing, and drying it.
[0066] The prepared activated carbon fiber composite material is added to a tannic acid solution. Tannic acid can etch the MOF crystals (such as ZI F-8 crystals) loaded on the activated carbon fiber, increase the specific surface area of the MOF crystals, and thereby improve the adsorption performance of the composite material for gaseous methyl iodide.
[0067] In some embodiments, the temperature of the heating reaction is 140-160° C., and the reaction time is 0.5-1.5 h.
[0068] In some embodiments, the concentration of the tannic acid solution is 0.02-0.03 g / mL. The tannic acid solution of this concentration can make the MOF crystals supported on the activated carbon fiber hollow due to etching, so that the specific surface area of the MOF crystals reaches the maximum.
[0069] The second aspect of the present invention provides an activated carbon fiber composite material prepared by the above-mentioned preparation method.
[0070] The third aspect of the present invention provides a use of the above-mentioned activated carbon fiber composite material in the preparation of an adsorption material.
[0071] In some embodiments, the adsorbent material is used to adsorb gaseous methyl iodide.
[0072] In some embodiments, the adsorbent material is used to adsorb gaseous methyl iodide under high humidity conditions.
[0073] The models and manufacturers of the instruments used in the various embodiments of this application are as follows:
[0074] Field emission electron scanning microscope (SEM), model: Drop Shape Analyzer 100, manufactured by Bruker, Germany;
[0075] The specifications and manufacturers of various raw materials used in the examples of this application are all commercially available except for the following special instructions:
[0076] Zinc nitrate hexahydrate (Zn(NO3)2·6H2O), with a specification of 99%, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0077] 2-Methylimidazole: specification is 99%, purchased from MacLean Biochemical Technology Co., Ltd.;
[0078] Anhydrous methanol: specification is 99.5%, purchased from Shanghai Runjie Technology Development Co., Ltd.;
[0079] Methyl iodide: specification is 99%, purchased from Nantong Feiyu Biotechnology Co., Ltd.;
[0080] Polysulfone (PSf) base membrane: purchased from Beijing Beichuang Qingyuan (Beijing) Technology Co., Ltd.; the PSf base membrane is formed by laminating a polysulfone layer and a non-woven fabric layer.
[0081] Tannic acid (TA): specification is 95%, purchased from McLean Biochemical Technology Co., Ltd.
[0082] Materials preparation:
[0083] (1) ACF preprocessing
[0084] First, the ACF was washed three times with deionized water, and then transferred to a 60°C forced air oven for drying for 12 h until fully dried, in order to wash away some oils and impurities loaded on the ACF during the production process, to avoid the subsequent impact on the loading of the MOF crystals.
[0085] (2) Preparation of metal ion solution
[0086] 0.8799 g of Zn(NO3)2·6H2O was added into 30 mL of deionized water and stirred evenly for 1 h at room temperature to obtain a metal ion solution.
[0087] (3) Preparation of organic ligand solution
[0088] 3.1147 g of 2-methylimidazole was added to 60 mL of anhydrous methanol and stirred evenly at room temperature for 1 h to obtain an organic ligand solution.
[0089] Example 1
[0090] The PSf base membrane was soaked in deionized water for 10 minutes and then dried in a 40°C forced air oven. The dried PSf base membrane was tightly fixed on the hollow frame with the smooth surface of the membrane (polysulfone layer side) facing upwards, and then the ACF was placed in the hollow frame with the PSf base membrane as a support, and then 30 mL of metal ion solution was poured onto one side of the ACF and soaked for 0.5 h to fully immerse the ACF in the metal ion solution.
[0091] After the immersion is completed, the excess metal ion solution is removed and the whole is transferred to a reactor containing 60 mL of organic ligand solution, ensuring that the solution level is higher than the PSf base membrane but not submerged. After sealing, it is placed in a 140°C forced air oven for reaction for 5 hours. After cooling to room temperature, the ACF is taken out, and the residual organic ligands are washed with anhydrous methanol, followed by drying in a 70°C vacuum oven for 12 hours to obtain the ZI F-8 / ACF-1 composite material.
[0092] The ZIF-8 / ACF-1 composite material obtained above was scanned by SEM, and the obtained SEM image is as follows: Figure 2 As shown, Figure 2 -(1) Figure 2 -(2) are SEM images of the composite material surface at 400nm and 5μm, respectively. It can be seen that when the ACF is left standing in the metal ion solution for 0.5h, the ZIF-8 crystals are almost non-existent on the ACF due to the short standing time, resulting in almost no adsorption effect of MOFs.
[0093] Example 2
[0094] The PSf base film was soaked in deionized water for 10 minutes and then dried in a 40°C forced air oven. The dried PSf base film was tightly fixed on the hollow frame with the smooth side of the film facing upwards, and then the ACF was placed in the hollow frame with the PSf base film as a support, and then 30 mL of metal ion solution was poured onto one side of the ACF and soaked for 1.5 h to fully immerse the ACF in the metal ion solution.
[0095] After the immersion is completed, the excess metal ion solution is removed and the whole is transferred to a reactor containing 60 mL of organic ligand solution, ensuring that the solution level is higher than the PSf base membrane but not submerged. After sealing, it is placed in a 140°C forced air oven for reaction for 5 hours. After cooling to room temperature, the ACF is taken out, and the residual organic ligands are washed with anhydrous methanol, followed by drying in a 70°C vacuum oven for 12 hours to obtain the ZI F-8 / ACF-2 composite material.
[0096] The ZIF-8 / ACF-2 composite material obtained above was scanned by SEM, and the obtained SEM image is as follows: Figure 3 As shown, Figure 3 -(1) and 3-(2) are SEM images of the composite material surface at 400nm and 5μm, respectively. It can be seen that when ACF is allowed to stand in the metal ion solution for 1.5h, the distribution of ZI F-8 on ACF is relatively dispersed, and the crystal form is good, and it is not easy to block the macropores of ACF. However, due to the short immersion time in the metal ion solution, the number of metal ions riveted on the ACF surface is small, resulting in too low ZI F-8 loading on ACF, which seriously affects the adsorption effect.
[0097] Example 3
[0098] The PSf base film was soaked in deionized water for 10 minutes and then dried in a 40°C forced air oven. The dried PSf base film was tightly fixed on the hollow frame with the smooth side of the film facing upwards, and then the ACF was placed in the hollow frame with the PSf base film as a support, and then 30 mL of metal ion solution was poured onto one side of the ACF and soaked for 2 hours to fully immerse the ACF in the metal ion solution.
[0099] After the immersion is completed, the excess metal ion solution is removed and the whole is transferred to a reactor containing 60 mL of organic ligand solution, ensuring that the solution level is higher than the PSf base membrane but not submerged. After sealing, it is placed in a 140°C forced air oven for reaction for 5 hours. After cooling to room temperature, the ACF is taken out, and the residual organic ligands are washed with anhydrous methanol. Then it is placed in a vacuum oven at 70°C and dried for 12 hours to obtain the ZI F-8 / ACF-3 composite material.
[0100] The ZIF-8 / ACF-3 composite material obtained above was scanned by SEM, and the obtained SEM image is as follows: Figure 4 As shown, Figure 4 -(1) and 4-(2) are SEM images of the composite material surface at 400nm and 5μm, respectively. It can be seen that when ACF is left to stand in the metal ion solution for 2h, the ZI F-8 grows evenly on the ACF with good crystal form. While exerting the adsorption effect of MOFs, the adsorption effect of ACF is also guaranteed. The two work together to achieve better adsorption selectivity.
[0101] Example 4
[0102] The PSf base film was soaked in deionized water for 10 minutes and then dried in a 40°C forced air oven. The dried PSf base film was tightly fixed on the hollow frame with the smooth side of the film facing upwards, and then the ACF was placed in the hollow frame with the PSf base film as a support, and then 30 mL of metal ion solution was poured onto one side of the ACF and soaked for 3 hours to fully immerse the ACF in the metal ion solution.
[0103] After the immersion is completed, the excess metal ion solution is removed and the whole is transferred to a reactor containing 60 mL of organic ligand solution, ensuring that the solution level is higher than the PSf base membrane but not submerged. After sealing, it is placed in a 140°C forced air oven for reaction for 5 hours. After cooling to room temperature, the ACF is taken out, and the residual organic ligand is washed with anhydrous methanol, followed by drying in a 70°C vacuum oven for 12 hours to obtain the ZI F-8 / ACF-4 composite material.
[0104] The ZIF-8 / ACF-4 composite material obtained above was scanned by SEM, and the obtained SEM image is as follows: Figure 5 As shown, Figure 5 -(1) and 5-(2) are SEM images of the composite material surface at 400nm and 1μm, respectively. It can be seen from the figures that when ACF is left in the metal ion solution for 3h, the distribution and accumulation of ZI F-8 on ACF is very serious, the crystal form is poor, and the macropores of ACF are seriously blocked. This is because the immersion time in the metal ion solution is too long, the number of metal ions riveted on the ACF surface is excessive, resulting in an excessively high ZI F-8 loading on the ACF, which seriously affects the adsorption effect.
[0105] Example 5
[0106] Soak the PSf base film in deionized water for 10 minutes and then dry it in a 40°C forced air oven. The dried PSf base film is tightly fixed on the hollow frame with the smooth side of the film facing up, and then the ACF is placed in the hollow frame with the PSf base film as a support. Then pour 30 mL of metal ion solution on one side of the ACF and soak it for 2 hours to fully immerse the ACF in the metal ion solution.
[0107] After the immersion is completed, the excess metal ion solution is removed, and the frame is moved to a stainless steel plate with the middle of the frame suspended in the air. 60 mL of organic ligand solution is poured into the stainless steel plate to ensure that the solution level is higher than the PSf base membrane but does not immerse the entire film. After standing at room temperature for 5 hours, the ACF is taken out and the residual organic ligand is washed with anhydrous methanol. Then, it is placed in a vacuum oven at 70°C and dried for 12 hours to obtain the ZI F-8 / ACF-5 composite material.
[0108] The ZIF-8 / ACF-5 composite material obtained above was scanned by SEM, and the obtained SEM image is as follows: Figure 6 As shown, Figure 6 -(1) and 6-(2) are SEM images of the composite surface at 3μm and 10μm, respectively. It can be seen from the figures that during the ligand back diffusion and metal heterogeneous nucleation growth at room temperature, due to the low temperature, the crystallinity of ZI F-8 on ACF is very low and it accumulates severely on ACF, which seriously restricts its methyl iodide adsorption performance.
[0109] Example 6
[0110] The PSf base film was soaked in deionized water for 10 minutes and then dried in a 40°C forced air oven. The dried PSf base film was tightly fixed on the hollow frame with the smooth side of the film facing upwards, and then the ACF was placed in the hollow frame with the PSf base film as a support, and then 30 mL of metal ion solution was poured onto one side of the ACF and soaked for 2 hours to fully immerse the ACF in the metal ion solution.
[0111] After the immersion is completed, the excess metal ion solution is removed and the whole is transferred to a reactor containing 60 mL of organic ligand solution, ensuring that the solution level is higher than the PSf base membrane but not submerged. After sealing, it is placed in a 100°C forced air oven for reaction for 5 hours. After cooling to room temperature, the ACF is taken out, and the residual organic ligand is washed with anhydrous methanol. Then it is placed in a vacuum oven at 70°C and dried for 12 hours to obtain the ZI F-8 / ACF-6 composite material.
[0112] The ZIF-8 / ACF-6 composite material obtained above was scanned by SEM, and the obtained SEM image is as follows: Figure 7 As shown, Figure 7 -(1) and 7-(2) are SEM images of the composite material surface at 400nm and 1μm, respectively. It can be seen that when the reaction temperature is 100℃, since the temperature has not yet reached the optimal crystallization temperature of ZI F-8, the distribution of ZI F-8 on ACF is relatively dispersed, the crystal shape is general, and the adsorption capacity is limited.
[0113] Example 7
[0114] The PSf base film was soaked in deionized water for 10 minutes and then dried in a 40°C forced air oven. The dried PSf base film was tightly fixed on the hollow frame with the smooth side of the film facing upwards, and then the ACF was placed in the hollow frame with the PSf base film as a support, and then 30 mL of metal ion solution was poured onto one side of the ACF and soaked for 2 hours to fully immerse the ACF in the metal ion solution.
[0115] After the immersion is completed, the excess metal ion solution is removed and the whole is transferred to a reactor containing 60 mL of organic ligand solution, ensuring that the solution level is higher than the PSf base membrane but not submerged. After sealing, it is placed in a 180°C forced air oven for reaction for 5 hours. After cooling to room temperature, the ACF is taken out, and the residual organic ligands are washed with anhydrous methanol. Then it is placed in a vacuum oven at 70°C and dried for 12 hours to obtain the ZI F-8 / ACF-7 composite material.
[0116] The ZIF-8 / ACF-7 composite material obtained above was scanned by SEM, and the obtained SEM image is as follows: Figure 8 As shown, Figure 8 -(1) and 8-(2) are SEM images of the composite material surface at 400nm and 5μm, respectively. It can be seen that when the reaction temperature is 180℃, the distribution and accumulation of ZIF-8 on ACF is very serious, the crystal form is poor, and the macropores of ACF are seriously blocked. This is because the reaction temperature is too high, the crystal form of MOFs is destroyed or even melted, which seriously affects the adsorption effect.
[0117] Example 8: Preparation of 1% TA@ZI F-8 / ACF-3 composite material by TA etching
[0118] The ZI F-8 / ACF-3 composite material prepared in Example 3 was placed in a reactor filled with a 1% TA solution, sealed and placed in a 150°C oven for reaction for 1 hour. After cooling to room temperature, the composite material was taken out, the residual TA was washed with anhydrous methanol, and dried in a vacuum oven at 70°C for 12 hours to obtain a 1% TA@ZI F-8 / ACF-3 composite material.
[0119] The 1%TA@ZI F-8 / ACF-3 composite material obtained above was scanned by SEM, and the obtained SEM image is as follows: Fig. 9 As shown, Fig. 9 -(1) and 9-(2) are SEM images of the composite surface at 400nm and 5μm, respectively. It can be seen that when the tannic acid concentration is 1%, there are etching marks on the ZI F-8 crystals, but the etching degree is low and has limited effect on further improving the methyl iodide adsorption performance of the composite material.
[0120] Example 9: Preparation of 2% TA@ZI F-8 / ACF-3 composite material by TA etching
[0121] The ZI F-8 / ACF-3 composite material prepared in Example 3 was placed in a reactor filled with a 2% TA solution, sealed and placed in a 150°C oven for reaction for 1 hour. After cooling to room temperature, the composite material was taken out, the residual TA was washed with anhydrous methanol, and dried in a vacuum oven at 70°C for 12 hours to obtain a 2% TA@ZI F-8 / ACF-3 composite material.
[0122] The 2%TA@ZI F-8 / ACF-3 composite material obtained above was scanned by SEM, and the obtained SEM image is as follows: Fig.10 As shown, Fig.10 -(1) and 10-(2) are SEM images of the composite surface at 400nm and 5μm, respectively. It can be seen that when the tannic acid concentration is 2%, the ZI F-8 crystals become hollow due to etching, and the etching degree is moderate, which can further improve the methyl iodide adsorption performance of the composite material.
[0123] Example 10: Preparation of 4% TA@ZI F-8 / ACF-3 composite material by TA etching
[0124] The ZI F-8 / ACF-3 composite material prepared in Example 3 was placed in a reactor filled with a 4% TA solution, sealed and placed in a 150°C oven for reaction for 1 hour. After cooling to room temperature, the composite material was taken out, the residual TA was washed with anhydrous methanol, and dried in a vacuum oven at 70°C for 12 hours to obtain a 4% TA@ZI F-8 / ACF-3 composite material.
[0125] The 4%TA@ZI F-8 / ACF-3 composite material obtained above was scanned by SEM, and the obtained SEM image is as follows: Fig.11 As shown, Fig.11 -(1) and 11-(2) are SEM images of the composite surface at 400nm and 5μm, respectively. It can be seen that when the tannic acid concentration is 4%, there are etching marks on the ZI F-8 crystals, but the etching degree is too high, resulting in the shedding of some ZI F-8 crystals, which will have a significant adverse effect on the methyl iodide adsorption performance of the composite material.
[0126] Test Case
[0127] The ZI F-8 / ACF composite materials prepared by different immersion times were placed in a tubular furnace and purged with N2 at 120°C for 2 hours. A small cup of methyl iodide was placed in a glass drying dish, covered with a lid, and placed in a 30°C constant temperature water bath for 1 hour to fully volatilize it. Next, the pretreated composite material was placed in a glass vial, then placed in a drying dish, and covered with a lid. At certain time intervals, the material was taken out and weighed, and the data was recorded and immediately put back. The weight of the material at each time point was subtracted from the weight of the pretreated composite material, and then divided by the weight of the pretreated composite material to obtain the methyl iodide adsorption amount per unit mass of the ZI F-8 / ACF composite material at different time points.
[0128] Performance measurement method
[0129] For the method for determining the static adsorption performance of gaseous methyl iodide, refer to the literature Zhang HP, Gong LL, Yin MJ, et al. Efficient organic iodide capture by a mesoporous biological-organic framework [J]. Cell Reports Physica l Science, 2022, 3(4): 100830. The weighing time points during the test are 10min, 20min, 30min, 40min, 50min, 60min, 70min, 80min, 100min, 120min, 140min, 170min, 200min, 230min, 270min, 310min, 350min, 400min, 450min, and 500min.
[0130] The amount of gaseous methyl iodide adsorbed at time point t is q t It can be expressed by the formula Calculated:
[0131] Where m t (g) is the total weight of the glass vial and the composite material therein at time point t, m1(g) is the total weight of the glass vial and the composite material therein before the test, m0(g) is the weight of the empty glass vial, and M t (g) is the weight of the blank control glass vial at time point t, M0(g) is the weight of the blank control glass vial before the test, q t The unit is (mg·g -1 ).
[0132] The static adsorption performance of gaseous methyl iodide of the ZI F-8 / ACF-1 composite material, ZI F-8 / ACF-2 composite material, ZI F-8 / ACF-3 composite material and ZI F-8 / ACF-4 composite material obtained in the above examples 1, 2, 3 and 4 was measured respectively. The measured data results are shown in FIG. Fig.12 shown.
[0133] It can be seen from the figure that the static adsorption of gaseous methyl iodide by the ZIF-8 / ACF-1 composite material, ZIF-8 / ACF-2 composite material, ZIF-8 / ACF-3 composite material, and ZIF-8 / ACF-4 composite material provided by the embodiment of the present invention all show an increasing trend with the increase of time. The static adsorption performance of gaseous methyl iodide by the ZIF-8 / ACF-3 composite material is better than that of the other three composite materials.
[0134] The static adsorption performance of gaseous methyl iodide of the ZI F-8 / ACF-3 composite material, ZI F-8 / ACF-5 composite material, ZI F-8 / ACF-6 composite material and ZI F-8 / ACF-7 composite material obtained in the above examples 3, 5, 6 and 7 was measured respectively. The measured data results are shown in Fig.13 shown.
[0135] As can be seen from the figure, the ZIF-8 / ACF-3 composite material of the present application, that is, the composite material with a standing time of 2 hours after adding metal ions and a reaction temperature of 140°C, has the best static adsorption performance of gaseous methyl iodide.
[0136] The static adsorption performance of gaseous methyl iodide of the 1% TA@ZI F-8 / ACF-3 composite material, 2% TA@ZI F-8 / ACF-3 composite material, and 4% TA@ZI F-8 / ACF-3 composite material obtained in Examples 8, 9, and 10 was measured respectively. The measured data results are shown in FIG. Fig.14 shown.
[0137] As can be seen from the figure, the static adsorption performance of gaseous methyl iodide of the 2% TA@ZI F-8 / ACF-3 composite material of the present application, that is, the static time after adding metal ions is 2 hours, the reaction temperature is 140°C, and the composite material etched with 2% tannic acid is the best.
[0138] In summary, the preparation method of a metal-organic framework / activated carbon fiber composite material of the present application improves the uniformity and firmness of the distribution of ZIF-8 on the surface and inside of ACF by utilizing the control effect of the PSf base film and the special effect of high temperature heating, selecting the appropriate immersion time and reaction temperature, and etching with tannic acid, and prepares a continuous and uniformly distributed metal-organic framework / activated carbon fiber composite material, overcoming the technical problems in the prior art that the metal-organic framework cannot effectively enter the inside of the activated carbon fiber and the metal-organic framework and the activated carbon fiber are not firmly combined. .
[0139] An activated carbon fiber composite material, a preparation method and its application in gaseous methyl iodide adsorption according to an embodiment of the present invention have at least one of the following advantages: the heterogeneous nucleation of MOFs on the activated carbon fiber is promoted, and the loading amount of MOFs on the activated carbon fiber is increased; the reaction rate of the ligand and the metal is effectively controlled, ensuring the good crystallinity of MOFs and preventing the loading amount of MOFs on the activated carbon fiber from being too high; by loading hydrophobic MOFs, the material has good gaseous methyl iodide adsorption performance under high humidity conditions.
[0140] The activated carbon fiber composite material, preparation method and application thereof in gaseous methyl iodide adsorption according to the embodiments of the present invention have the following advantages:
[0141] (1) The present invention utilizes the control effect of the PSf-based membrane and adopts a high-temperature assisted ligand reverse diffusion strategy to allow the organic ligand solution to slowly penetrate and diffuse into the ACF, effectively controlling the reaction rate of the ligand and the metal, ensuring the good crystallinity of MOFs (such as ZIF-8) while improving the uniformity and firmness of the distribution of MOFs on the surface and inside of the ACF. The obtained activated carbon fiber composite material has good gaseous methyl iodide adsorption performance under high humidity conditions.
[0142] (2) The present invention cleverly uses a hollow frame to separate the activated carbon fibers with metal ions fixed thereto from the organic ligand solution, thereby avoiding homogeneous nucleation between the metal ions and the organic ligands, better controlling the reaction rate between the ligands and the metal, and being more conducive to improving the uniformity of the distribution of MOFs on the surface and inside of the ACF.
[0143] (3) The present invention further adopts tannic acid etching, and controls the concentration of the tannic acid solution, the reaction temperature and the time to make the MOFs crystals loaded on the activated carbon fiber hollow due to etching, so that the specific surface area of the ZI F-8 crystals reaches the maximum.
Claims
1. A method for preparing an activated carbon fiber composite material, characterized in that: The preparation method comprises the following steps: S1. Using a metal ion solution to soak the activated carbon fiber, so that the metal ions in the metal ion solution are evenly riveted on the activated carbon fiber; S2. The activated carbon fibers fixed with metal ions obtained in step S1 are placed on the polysulfone layer of the polysulfone-based membrane, and then the other layer of the polysulfone-based membrane is placed downward in the organic ligand solution so that the organic ligand solution immerses the polysulfone-based membrane but does not contact the activated carbon fibers. Then, a coordination reaction is carried out under sealing conditions to obtain an activated carbon fiber composite material.
2. The preparation method according to claim 1, characterized in that: The metal ion solution is one of zinc nitrate hexahydrate solution, cobalt nitrate hexahydrate solution and copper sulfate pentahydrate solution, and the ligand solution is a methanol solution of 2-methylimidazole.
3. The preparation method according to claim 1, characterized in that: The polysulfone-based membrane is formed by laminating a polysulfone layer and a non-woven fabric layer.
4. The preparation method according to claim 1, characterized in that: In step S1, the soaking time is 1.5-2.5 hours.
5. The preparation method according to claim 1, characterized in that: Step S2 specifically includes the following steps: S21. The polysulfone-based membrane is fixed to the hollow frame, wherein the polysulfone layer of the polysulfone-based membrane faces upward; S22. The activated carbon fiber obtained in step S1 is placed on the polysulfone layer of the polysulfone-based membrane, and then translated into a reactor containing an organic ligand solution, so that the organic ligand solution submerges the polysulfone-based membrane, but the liquid level does not exceed the height of the hollow frame; S23. The reactor is sealed and placed in an oven for coordination reaction. After the reaction is completed, it is cooled to room temperature to obtain the activated carbon fiber composite material.
6. The preparation method according to claim 1, characterized in that: In step S2, the coordination reaction is carried out at a temperature of 120°C-160°C and for a time of 2-4 hours.
7. The preparation method according to claim 1, characterized in that: The preparation method further comprises: The activated carbon fiber composite material prepared in step S2 is placed in a tannic acid solution, and heated to react under a sealed condition. After the reaction is completed, the activated carbon fiber composite material is taken out.
8. The preparation method according to claim 7, characterized in that: The concentration of the tannic acid solution is 0.02-0.03 g / mL, the temperature of the heating reaction is 140-160° C., and the reaction time is 0.5-1.5 h.
9. An activated carbon fiber composite material prepared according to the preparation method according to any one of claims 1 to 8.
10. Use of the activated carbon fiber composite material according to claim 9 in preparing an adsorption material, wherein the adsorption material is used for adsorbing gaseous methyl iodide.